Long non-coding RNAs in bone metastasis: progresses and perspectives as potential diagnostic and prognostic biomarkers - Maroni, Paola; Gomarasca, Marta; Lombardi, Giovanni (Frontiers in Endocrinology, 2023)
In a precision medicine perspective, among the biomarkers potentially useful for early diagnosis of cancers, as well as to define their prognosis and eventually to identify novel and more effective therapeutic targets, there are the long non-coding RNAs (lncRNAs). The term lncRNA identifies a class of non-coding RNA molecules involved in the regulation of gene expression that intervene at the transcriptional, post-transcriptional, and epigenetic level. Metastasis is a natural evolution of some malignant tumours, frequently encountered in patients with advanced cancers. Onset and development of metastasis represents a detrimental event that worsen the patient’s prognosis by profoundly influencing the quality of life and is responsible for the ominous progression of the disease. Due to the peculiar environment and the biomechanical properties, bone is a preferential site for the secondary growth of breast, prostate and lung cancers. Unfortunately, only palliative and pain therapies are currently available for patients with bone metastases, while no effective and definitive treatments are available. The understanding of pathophysiological basis of bone metastasis formation and progression, as well as the improvement in the clinical management of the patient, are central but challenging topics in basic research and clinical practice. The identification of new molecular species that may have a role as early hallmarks of the metastatic process could open the door to the definition of new, and more effective, therapeutic and diagnostic approaches. Non-coding RNAs species and, particularly, lncRNAs are promising compounds in this setting, and their study may bring to the identification of relevant processes. In this review, we highlight the role of lncRNAs as emerging molecules in mediating the formation and development of bone metastases, as possible biomarkers for cancer diagnosis and prognosis, and as therapeutic targets to counteract cancer spread.